AN INTEGRATING IPUSNAS TO ASSIST INNOVATIVE READING STRATEGY TO DEVELOP READING COMPREHENSION FOR EFL STUDENTS: A NARRATIVE INQUIRY - Annisa Ryani Fitri (IKIP Siliwangi, 2022)
To improve the quality of education, teachers and stakeholders need to innovate education. In carrying out innovation, teachers can integrate technology as a tool for innovation in learning. IPusnas as a medium for learning to read English can help teachers and students improve their reading comprehension. This research was conducted to determine students' experiences with improving reading comprehension in English through the iPusnas application. Students' experience of being kidnapped through a humanistic approach with interview techniques and questionnaires was carried out in the eleventh grade at SMK Insan Tazakka Cikampek. The study results indicate that iPusnas can help teachers innovate to improve student learning quality. In addition, student activity and student learning performance increased. It is due to the student's interest in interactive media used by the teacher. Keywords: Innovation, iPusnas, Reading Comprehension